The quantum tunnel effect from the point of view of quantum mechanics and classical physics - Kondratenko, A.; Kostenko, V.; Shkoda, V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
Parallel analyses of matter penetrating a barrier are analyzed, one using electrodynamics, the other using quantum mechanics. Mathematical operations are performed to show the identical nature of the phenomena of reflection above the barrier and of penetration of the barrier in quantum mechanics and in classical electrodynamics. It is shown that, in reality, the tunneling effect is not a “purely quantum phenomenon”. Проведено параллельное рассмотрение прохождения материи через барьер методами электродинамики и квантовой механики. Математически строго получена абсолютная идентичность надбарьерного отражения и подбарьерного прохождения, как в квантовой механике, так и в классической электродинамике. Показано, что определение туннельного эффекта как «чисто квантового явления» – не соответствует действительности. Проведено паралельне дослідження проходження матерії через бар’єр методами електродинаміки та квантової механіки. Математично виключно отримана абсолютна ідентичність надбар’єрного відбиття та підбар’єрного проходження як у квантовій механіці так і в класичній електродинаміці. Показано, що визначення тунельного ефекту як «чисто квантового явища» – не відповідає дійсності.
Keywords: quantum mechanics; barrier; penetration; reflection; tunnel effect; квантовая механика; барьер; прохождение; отражение; туннельный эффект